Tourists’ intentions to participate in coffee tourism in the context of local Turkish coffee culture - Demir, Yeliz; Bertan, Serkan (Anais Brasileiros de Estudos Turísticos, 2024)
The research aims to determine the factors affecting tourists’ intention to visit destinations where local Turkish coffee varieties are available. The research sample is made up of local tourists. The data was collected by survey and the number of participants reached by convenience sampling method was 308. The study conducted validity, reliability, confirmatory factor analysis, and path analysis to test the hypotheses. According to the results obtained in the research, tourist experience has a statistically significant and positive influence on destination image and perceived value. Destination image positively influences novelty seeking and perceived value. Novelty seeking positive influences on perceived value and visit intention. Finally, visit perception partially mediates between visit intention and destination image. Research results show that local tourists intend to participate in coffee tourism. In this case, local Turkish coffee varieties should be considered by practitioners as an important resource for coffee tourism in Türkiye. In the future, researchers can study foreign tourists’ intentions to participate in coffee tourism in Türkiye.